Desenvolvimento de interface homem-máquina para a avaliação de sinais motores da doença de Parkinson - Rosa, Rodrigo Ramos (2022)
Parkinson's disease (PD) is a chronic and progressive neurodegenerative disorder for which there is currently no cure. PD causes distinct motor symptoms such as bradykinesia, rigidity, and tremor. Physical therapy, i.e., rehabilitation, psychological, drug, and surgical intervention are all used to treat the disease. Clinical assessments using subjective scales have been used to make diagnoses and assess disease severity. Several studies and technologies for objectively assessing PD have been developed in recent years. In this context, the goal of this work was to create a wearable and mobile Human Machine Interface (HMI) capable of being used for the evaluation, rehabilitation, and monitoring of motor signs in people with PD. With the positive diagnosis for PD, the treatment begins, which is broad, and involves the use of medications, as well as the performance of surgery, physical therapy, and psychological monitoring. Physical therapy is fundamental in the patient's rehabilitation process, allowing the maximization of functional abilities and minimizing secondary complications. The use of serious games (JS) in the rehabilitation of individuals with neurological disorder, has proven effective. In this context JS is used with educational and training character. When rehabilitation is based on JS, a Human Machine Interface (HMI) is an important part of the whole process, since the user needs to interact with the game in an appropriate way for the rehabilitation to achieve the desired success. In the context of PD and JS, studies seek to demonstrate the effectiveness of the use of game sensors available on the market. Among them we can mention the Nintendo Wiimote, Microsoft's Kinect, Sony Playstation Eye, and even the use of common webcams. These sensors are easily found in the national market and with accessible prices. However, these sensors were not used, because the present study proposes the use of an HMI capable of being used as a serious game sensor and also to provide data for evaluation and monitoring of motor symptoms, such as bradykinesia and tremor, and the commercial sensors cited do not meet all the requirements of the proposed system. We found examples such as the model "Prime X Gloves" from the manufacturer MANUSTM, however, this device is not available in the Brazilian market and has a high cost (over 4 thousand dollars). In effect, the best option was to develop the device itself, so that all the system requirements were met, including being a low-cost device. The device, which was based on inertial sensors, was used to measure the rotational movements of the wrist. The device was used in a serious game to obtain information from the orientation of the user's hand and to control the game. During the procedure, the inertial sensor measurements were recorded and later used to assess the motor condition of patients with PD. The results were satisfactory, and the device established itself as an important component of the serious game, facilitating interaction between "man," i.e., users, and "machine," i.e., computer. The collected data were processed, and the feasibility of evaluating the patients' motor signs was confirmed as a result. The possibility of implementing and using a wearable and mobile HMI was demonstrated to monitor motor signs from PD patients through serious game. The use of wrist’s rotation angles showed to be effective for the evaluation of motor condition, opening a possibility for longitudinal monitoring of motor signs.